Literature Review: Hubungan Pekerjaan dan Penghasilan Keluarga dengan Kejadian Kurang Energi Kronik Pada Ibu Hamil - Dwike An Nisa Kurniawan; Triawanti Triawanti; Meitria Syahadatina Noor; Djallalluddin Djallalluddin; Nur Qamariah (Homeostasis, 2021)
Abstract: Chronic lack of energy is the condition of pregnant women who lack food intake so that they experience long-lasting poor nutritional status. A person’s condition is said to be less chronic energy if the measurement results of the circumference of his than 23,5 cm. Writing this literature review is intended to summarize what is known about the relationship between work and family income with the incidence of KEK in pregnant women. The method used is narrative review by analyzing several related journals. There are 20 journals included in the literature review. The research reviewed showed that 45% conducted research on occupational variables with KEK and 85% conducted statistical test on the relationship between family income and KEK. The results that work (66,67%) and family income (64,71%) have a relationship with KEK in pregnant women. Keywords: work, family income, lack of chronic energy, pregnant women. Abstrak: Kurang energi kronik adalah keadaan ibu hamil yang kekurangan asupan makanan sehingga mengalami status gizi buruk yang berlangsung lama. Keadaan seseorang dikatakan kurang energi kronik jika hasil pengukuran lingkar lengan atasnya kurang dari 23,5 cm. Penulisan literature review ini ditujukan untuk merangkum hal yang diketahui tentang hubungan pekerjaan dan penghasilan keluarga dengan kejadian KEK pada ibu hamil. Metode yang digunakan narrative review dengan menganalisa beberapa jurnal terkait. Ada 20 jurnal disertakan dalam literature review. Data penelitian yang direview menunjukkan 45% melakukan penelitian variabel pekerjaan dengan KEK dan 85% yang melakukan uji statistik hubungan penghasilan keluarga dengan KEK. Hasil menunjukkan bahwa pekerjaan (66,67%) dan penghasilan keluarga (64,71%) memiliki hubungan dengan KEK pada ibu hamil. Kata-kata kunci: pekerjaan, penghasilan keluarga, kurang energi kronik, ibu hamil.